Energy and exergy analyses of coconut drying in a solar tunnel drier. (October 2021) - Ayyappan, S; Selvakumar, M; Muthukannan,; Karunaraja,; Ram Kumar, T
This paper presents energy and exergy analyses of solar drying of coconuts in a hemispherical solar tunnel drier. Coconuts were dried from an initial moisture content of about 55% (w.b.) to 7% (w.b.) in the solar tunnel drier in 60 hrs whereas the open sun drying process takes 153 hrs for reducing the moisture content to the same level. The drying experiments were conducted at a mass flow rate of 7.25 kg/s with an average air velocity of 0.1 m/s. Using the first law of thermodynamics, energy analysis was carried out to estimate the amount of energy received by the solar tunnel drier and the ratios of energy utilization. However, exergy analysis was accomplished to determine the exergy loss and exergy efficiency by applying the second law of thermodynamics. Energy utilization, energy utilization ratio, exergy inflow and exergy loss in the drier were studied and these values are found to be increased with increasing solar radiation. The exergy inflow and exergy loss in the drier varied between 0.194 kJ/s–8.18 kJ/s and 0.085 kJ/s–5.377 kJ/s respectively. The exergy efficiency of the drier varied between 23.6%–53%.